Dominant Antiviral CD8+ T Cell Responses Empower Prophylactic Antibody-Eliciting Vaccines Against Cytomegalovirus - Pardieck, Iris N.; van Duikeren, Suzanne; Veerkamp, Dominique M. B.; Brasem, Dena J.; Redeker, Anke; van Bergen, Jeroen; Han, Wanda; Ossendorp, Ferry; Zondag, Gerben; Arens, Ramon (Frontiers in Immunology, 2022)
Human cytomegalovirus (HCMV) is an ubiquitous herpesvirus that can cause serious morbidity and mortality in immunocompromised or immune-immature individuals. A vaccine that induces immunity to CMV in these target populations is therefore highly needed. Previous attempts to generate efficacious CMV vaccines primarily focused on the induction of humoral immunity by eliciting neutralizing antibodies. Current insights encourage that a protective immune response to HCMV might benefit from the induction of virus-specific T cells. Whether addition of antiviral T cell responses enhances the protection by antibody-eliciting vaccines is however unclear. Here, we assessed this query in mouse CMV (MCMV) infection models by developing synthetic vaccines with humoral immunity potential, and deliberately adding antiviral CD8+ T cells. To induce antibodies against MCMV, we developed a DNA vaccine encoding either full-length, membrane bound glycoprotein B (gB) or a secreted variant lacking the transmembrane and intracellular domain (secreted (s)gB). Intradermal immunization with an increasing dose schedule of sgB and booster immunization provided robust viral-specific IgG responses and viral control. Combined vaccination of the sgB DNA vaccine with synthetic long peptides (SLP)-vaccines encoding MHC class I-restricted CMV epitopes, which elicit exclusively CD8+ T cell responses, significantly enhanced antiviral immunity. Thus, the combination of antibody and CD8+ T cell-eliciting vaccines provides a collaborative improvement of humoral and cellular immunity enabling enhanced protection against CMV.